Right-to-Medicines Litigation and Universal Health Coverage: Institutional Determinants of the Judicialization of Health in Brazil - Mariana P. Socal; Joseph J. Amon; João Biehl (Harvard FXB Center for Health and Human Rights, 2020)
Over the past three decades, Brazil has developed a decentralized universal health system and achieved significant advances in key health indicators. At the same time, Brazil's health system has struggled to ensure equitable and quality health services. One response to the broad promises and notable shortcomings has been a sharp rise in right-to-health litigation, most often seeking access to medicines. While much has been written about the characteristics of patient-plaintiffs and the requested medicines in right-to-health litigation in Brazil, little research has examined potential community-level and institutional drivers of judicialization and their role as mechanisms of accountability. To explore these dimensions, we used a mixed-effects analytical model to examine a representative sample of lawsuits for access to medicines filed against the state of Rio Grande do Sul in 2008. We found that the presence of a Public Defender's Office was associated with a sevenfold increase in the likelihood of a municipality having a medicine-requesting lawsuit. This effect was maintained after controlling for a series of municipality characteristics. As low- and middle-income countries seek to achieve universal health coverage within the framework of the Sustainable Development Goals, Brazil's experience may be illustrative of the challenges that health systems will face and the institutional mechanisms that will emerge, advancing accountability and individual patients' interests in response.